Ratios between circulating myeloid cells and lymphocytes are associated with mortality in severe COVID-19 patients - Ma Hui (De Gruyter, 2021)
Recent studies indicate that host immune responses are dysregulated with either myeloid cell compartment or lymphocyte composition being disturbed in COVID-19. This study aimed to assess the impact of SARS-CoV-2 viral infection on the composition of circulating immune cells in severe COVID-19 patients. In this retrospective single-center cohort, 71 out of 87 COVID-19 patients admitted to the intense care unit for oxygen treatment were included in this study. Demographics, clinical features, comorbidities, and laboratory findings were collected on admission. Out of the 71 patients, 5 died from COVID-19. Compared with survived patients, deceased patients showed higher blood cell counts of neutrophils and monocytes but lower cell counts of lymphocytes. Intriguingly, the neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and basophil-to-lymphocyte ratio (BLR) were markedly higher in deceased patients compared to survived patients. Furthermore, the lymphocyte counts were negatively correlated with D-dimer levels, while the ratios between myeloid cells and lymphocyte (NLR, MLR, and BLR) were positively correlated with D-dimer levels. Our findings revealed that the ratios between myeloid cells and lymphocytes were highly correlated with coagulation status and patient mortality in severe COVID-19.